Morphology controlled fabrication of zinc phosphate hierarchical microspheres for room temperature ammonia gas sensor - Khalida Akhtar; Naila Zubair; Neelam Zeb; Syed Sajjad Ali Shah; Zia Ullah Khan; Hina Khalid (Sensors and Actuators Reports)
Hierarchical Zinc phosphate nano/microstructures with controlled morphological features were synthesized in aqueous solutions through simple and economical route without using any type of surfactant or template. SEM analysis revealed novel morphologies of the synthesized powders i.e., hierarchical microspheres, urchin like microspheres, nanoflowers and nanoellipsoids and unfolded that produced morphologies strongly depended upon the applied experimental conditions. Selected batches of the synthesized powders i.e., hierarchical microspheres, urchin like microspheres and hierarchical nanoellipsoids were selected for further analysis using XRD, FT-IR, BET analysis and gas sensing application and termed as Zinc Phosphate 1 (ZP1), Zinc Phosphate 2 (ZP2), and Zinc Phosphate 3 (ZP3), respectively. XRD results confirmed the crystalline nature of the as-prepared powders with crystallite sizes 16.5 nm, 30. 15 nm and 37.01 nm, for ZP1, ZP2 and ZP3, respectively. Evaluation of gas sensing properties of the selected samples revealed that sensors based on ZP1 showed highest gas sensing response of 89 % with response recovery time 31/12 s, towards 5 ppm ammonia at room temperature. In addition, the lowest detection limit was investigated to be <1 ppm. Because of the excellent gas sensing performance, the synthesized zinc phosphate structures could be employed as promising candidates for developing highly sensitive and selective room temperature ammonia gas sensor.